Antimicrobial Regimens Prescribed by Canadian Physicians for Chemotherapy-Induced Febrile Neutropenic Episodes. (1999) - Laverdière, Michel; Bow, Eric J; Rotstein, Coleman; Ioannou, Stratis; Carr, Danielle; Moghaddam, Narguess; the Canadian Fluconazole Study Group,
Abstract : OBJECTIVE: To study the antimicrobial management of cancer patients with chemotherapy-induced neutropenia by Canadian physicians. SETTING: A cohort of 274 cancer patients with severe neutropenia (ie, less than 0.5×10 9 neutrophils/L) who participated in a prospective double-blind, placebo controlled study on antifungal prophylaxis conducted in 14 Canadian university-affiliated centres. Antifungal prophylaxis (oral fluconazole 400 mg daily) was administered to 153 of 274 (56%) patients. RESULTS: Antibacterial prophylaxis with a quinolone was given to 87 patients (32%) at the onset of chemotherapy whereas trimethoprim/sulphamethoxazole was given to 56 (20%) patients. Fever (ie, 38°C or over) occurred in 216 (79%) patients after a median duration of neutropenia of four days (range one to 31 days). Empirical antibacterial antibiotics were administered in 214 febrile patients. In 164 (77%) patients antibiotics were started during the first 24 h of fever. Monotherapy with a third generation cephalosporin and duotherapy with a antipseudomonal beta-lactam and an aminoglycoside were prescribed in 69 (32%) and 61 (28%) of the febrile patients, respectively. Inclusion of vancomycin in the initial empirical regimen was noted in 32 (15%) patients. Modifications of the initial regimen occurred in 187 (87%) patients after a median of five days (range one to 28 days). Empirical systemic amphotericin B was added after a median duration of nine days (range one to 34 days) of the empirical antibacterial regimen. CONCLUSIONS: Overall, the antimicrobial management of cancer patients with chemotherapy-induced neutropenia by Canadian physicians follows the current guidelines promulgated by the Infectious Diseases Society of America.